A TOGAF 10-Based Enterprise Architecture Framework for Digital Transformation in SME Banks - Sari, Laras Ayu Ditya; Mulyana, Rahmat; Mukti, Iqbal Yulizar (Jurnal Teknik Informatika (Jutif), 2025)
The banking sector faces significant challenges in implementing Digital Transformation (DT), particularly among Bank Perekonomian Rakyat (BPR), which serves as SME banks in Indonesia. These institutions often struggle with infrastructure limitations, technological adoption, and regulatory compliance. While existing research extensively examines DT strategies and Enterprise Architecture (EA) frameworks in large-scale banking institutions, their application to smaller banks like BPR remains underexplored. This study addresses this gap by developing an EA- based solution tailored to BPRDCo, a representative SME bank. Using the Design Science Research (DSR) methodology, the study follows five structured stages: problem explication, requirement specification, design and development, demonstration, and evaluation. The framework leverages the TOGAF Standard 10th Edition, integrating best practices across business, information systems, and technology architectures. The resulting EA blueprint provides a structured guide for DT implementation, aligning business and IT strategies while ensuring regulatory compliance. This study contributes to the EA knowledge base and offers practical implications for SME banks to enhance operational efficiency, optimize resource utilization, and strengthen competitiveness in the evolving financial landscape. By offering a systematic approach DT, this research advances knowledge in IT governance, architecture modeling, and system integration. Moreover, it provides a replicable framework that can inform future developments in digital banking solutions, reinforcing the importance of EA as a strategic tool for sustainable technological innovation.